2020
DOI: 10.1002/aoc.6037
|View full text |Cite
|
Sign up to set email alerts
|

Divalent manganese, cobalt, copper and cadmium complexes of (Z)‐N‐benzoyl‐N′‐(1H‐1,2,4‐triazol‐3‐yl)carbamimidothioic acid: Preparation, characterization, computational and biological studies

Abstract: In this work, (Z)-N-benzoyl-N 0-(1H-1,2,4-triazol-3-yl)carbamimidothioic acid and its Mn(II), Co(II), Cu(II) and Cd(II) complexes were introduced for the first time. This carbonyl thiourea ligand was prepared by the reaction of 1H-1,2,4-triazol-3-amine with benzoyl isothiocyanate. The structural elucidation of these compounds was performed using elemental analysis and spectral and magnetic measurements. Octahedral structures of all complexes, except Cd(II) complex with a tetrahedral geometry, were confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The observed IC 50 values revealed that the compounds were effective against breast cancer cells, similar to values previously reported for other Co-containing complexes. 52 Compared to the ligands, the cobalt complex showed slightly better cytotoxicity, and this could be ascribed to the existence of cobalt ions that synergistically augmented the cytotoxicity. These results were similar to the observed breast cancer cell toxicity we have previously reported for another Co complex.…”
Section: Resultsmentioning
confidence: 98%
“…The observed IC 50 values revealed that the compounds were effective against breast cancer cells, similar to values previously reported for other Co-containing complexes. 52 Compared to the ligands, the cobalt complex showed slightly better cytotoxicity, and this could be ascribed to the existence of cobalt ions that synergistically augmented the cytotoxicity. These results were similar to the observed breast cancer cell toxicity we have previously reported for another Co complex.…”
Section: Resultsmentioning
confidence: 98%
“…[ 34 ] Finally, some Cd‐CCs mimic organophosphate pesticide degrading enzymes [ 35 ] and show potent antioxidant properties. [ 36–39 ]…”
Section: Introductionmentioning
confidence: 99%